The art of scalability scalable web architecture, processes, and organizations for the modern enterprise - Abbott, Martin L.; Fisher, Michael T. (Addison-Wesley, 2015)
A Comprehensive, Proven Approach to IT Scalability from Two Veteran Software, Technology, and Business Executives In this second edition of The Art of Scalability , AKF Partners cofounders Martin L. Abbott and Michael T. Fisher cover everything product, technology and business leaders must know to build products that can scale smoothly to meet any business requirement. Drawing on their unparalleled experience managing some of the world's highest-transaction-volume Web sites, the authors provide detailed models and best-practice approaches available in no other book. Unlike previous books on scalability, The Art of Scalability doesn't limit its coverage to technology. Writing for both technical and nontechnical decision-makers, this book covers everything that impacts scalability, including architecture, processes, people, and organizations. This second edition has been edited to improve readability and includes new and updated content, a new chapter on Agile architecture, and new case studies. Throughout, the authors address a broad spectrum of real-world challenges, from performance testing to IT governance. Using their tools and guidance, organizations can systematically overcome obstacles to scalability and achieve unprecedented levels of technical and business performance. New and Updated Coverage includes · Staffing the scalable organization: essential organizational, management, and leadership skills for technical leaderswith a special focus on how to build truly Agile organizations. · How to organize teams to maximize innovation and reduce value destroying team conflict. · Building processes for scale: process lessons from hyper-growth companies, from technical issue resolution to crisis management · How to manage risk and how to create effective change management in the age of continuous deployment. · Architecting scalable solutions: powerful proprietary models for identifying scalability needs and choosing the best approaches to meet them · How to practice "Agile" Architecture · Optimizing performance through caching, application and database splitting, and asynchronous design · New and updated scalability techniques for emerging technologies, including clouds and grids · Planning for rapid data growth and new data centers · Evolving monitoring strategies to tightly align with customer requirements.
Includes index. - Online resource; title from title page (Safari, viewed June 11, 2015)
Keywords: Web site development; Computer networks -- Scalability; Business enterprises -- Computer networks; Sites Web; Développement; Réseaux d'ordinateurs; Extensibilité; Entreprises; Réseaux d'ordinateurs; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Business enterprises; Computer networks; Computer networks; Scalability